2016
DOI: 10.1146/annurev-publhealth-032315-021507
|View full text |Cite
|
Sign up to set email alerts
|

Rural Health Care Access and Policy in Developing Countries

Abstract: Compared to their urban counterparts, rural and remote inhabitants experience lower life expectancy and poorer health status. Nowhere is the worldwide shortage of health professionals more pronounced than in rural areas of developing countries. Sub-Saharan Africa (SSA) includes a disproportionately large number of developing countries; therefore, this article explores SSA in depth as an example. Using the conceptual framework of access to primary health care, sustainable rural health service models, rural heal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
166
0
13

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 217 publications
(186 citation statements)
references
References 62 publications
7
166
0
13
Order By: Relevance
“…Therefore, gentamicin should be used whenever clinically indicated. In several resource limited countries like Tanzania, there is limited availability of medications (28,29), thus obliging prescribers to prescribe whatever is available. The fact that only 57% of tested antibiotics exerted significant antibacterial activities against the uropathogenic bacteria, shows that there is no universal remedy for treatment of UTI during pregnancy.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, gentamicin should be used whenever clinically indicated. In several resource limited countries like Tanzania, there is limited availability of medications (28,29), thus obliging prescribers to prescribe whatever is available. The fact that only 57% of tested antibiotics exerted significant antibacterial activities against the uropathogenic bacteria, shows that there is no universal remedy for treatment of UTI during pregnancy.…”
Section: Discussionmentioning
confidence: 99%
“…The earlier mention of the plaudit from the World Bank about Thailand's development is also applicable and can equally be applied to the progress made in the Thai health system over the last few decades. That improvement confirms that Thailand is performing at a higher level than many of its counterpart nations and indeed has been innovative in adopting contemporary health policy into practice (Balabanova et al, 2011;Strasser et al, 2016). This progressive public policy approach and the achievements over time have been significant.…”
Section: Progressive Health Reformmentioning
confidence: 81%
“…Rural areas have both lower densities of health workers and less-educated workforce [6]. Achieving the equitable BPHS for all residents requires that every Chinese family in rural and urban areas has access to an appropriately trained and supported health worker.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have revealed that most PHCWs, especially village doctors, have poor education and insufficient competency to provide high quality service [4,5]. One important strategy to improve the competency of PHCWs is training [6]. At present, the main training mode for PHCWs is the traditional face-to-face training [7], but its inflexibility, time constraints, travel costs, and limited training opportunities have negative effects on training [8,9].…”
Section: Introductionmentioning
confidence: 99%